Surgical robot-assisted tripod percutaneous reconstruction technique combined with bone cement filling technique for the treatment of acetabular metastasis - Huang, Zhen; Zhu, Kun-Peng; Hu, Jian-Ping; Zhu, Yu-Run; Xu, En-Jie; Ma, Xiao-Long; Wang, Yong-Jie; Zhang, Chun-Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Acetabular metastasis is a type of metastatic bone cancer, and it mainly metastasizes from cancers such as lung cancer, breast cancer, and renal carcinoma. Acetabular metastasis often causes severe pain, pathological fractures, and hypercalcemia which may seriously affect the quality of life of acetabular metastasis patients. Due to the characteristics of acetabular metastasis, there is no most suitable treatment to address it. Therefore, our study aimed to investigate a novel treatment technique to relieve these symptoms. Methods: Our study explored a novel technique to reconstruct the stability of the acetabular structure. A surgical robot was used for accurate positioning and larger-bore cannulated screws were accurately inserted under the robot’s guidance. Then, the lesion was curetted and bone cement was injected through a screw channel to further strengthen the structure and kill tumor cells. Results: A total of five acetabular metastasis patients received this novel treatment technique. The data relating to surgery were collected and analyzed. The results found that this novel technique can significantly reduce operation time, intraoperative bleeding, visual analogue score scores, Eastern Cooperative Oncology Group scores, and postoperative complications (e.g., infection, implant loosening, hip dislocation) after treatment. Follow-up time ranged from 3 months to 6 months, and the most recent follow-up results showed that all patients survived and no acetabular metastasis progressed in any of the patients after surgery. Conclusion: Surgical robot-assisted tripod percutaneous reconstruction combined with the bone cement filling technique may be a novel and suitable treatment in acetabular metastasis patients. Our study may provide new insights into the treatment of acetabular metastasis.